Phosphorus-containing macromolecular charring agent as well as preparation method and application thereof
The phosphorus-containing macromolecule carbon-forming agent prepared by two-equivalent esterification methods solves the shortcomings of the existing DOPO derivative flame retardant in the polyester system, significantly improves the flame retardant and mechanical properties, overcomes the wick effect, and meets the UL-94 V-0 test standard.
Patent Information
- Application Number
- CN202510345210.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-24
AI Technical Summary
The existing DOPO derivative flame retardants have problems such as complex reaction system, low molecular weight, low thermal decomposition temperature, and significant wick effect in the polyester system, which is difficult to meet the flame retardant requirements of glass fiber reinforced polyester composite materials.
The phosphorus-containing macromolecule carbon-forming agent was prepared by two esterification methods, and the phosphorus-containing macromolecule carbon-forming agent was esterified by DOPO diol derivatives and adipic acid, followed by esterification reaction with 1,3,5-tris(2-hydroxyethyl) isocyanurate, and the terminal carboxylic sodium salting was carried out to produce a phosphorus-containing macromolecule carbon-forming agent with high molecular weight and controllable structure.
It significantly improves the flame retardant performance of polyester materials, overcomes the wick effect in glass fiber reinforced systems, meets the UL-94 V-0 test standards, and maintains high mechanical properties.
Smart Images

Figure CN119859252A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardants and relates to a phosphorus-containing macromolecular carbonizing agent and a preparation method and application thereof. Background Art
[0002] Polyester resin is one of the most commonly used thermoplastic resins. With its advantages of easy processing, good acid and alkali resistance, and high chemical stability, it has been widely used in plastic packaging, synthetic fibers, automotive parts and other fields. However, polyester contains a large amount of C, H, and O elements in its molecular structure, and has a low ignition point, which makes it extremely easy to burn and the fire spreads quickly, and its flame retardant performance is poor. Therefore, flame retardant modification of polyester has become the focus of researchers.
[0003] In the application of polyester materials, glass fiber reinforced polyester composites are highly favored due to their excellent mechanical properties (such as strength, rigidity, etc.). However, the introduction of glass fiber has brought about a significant wick effect problem. The wick effect refers to the fact that when burning, the polyester matrix is heated and melted, and the melt quickly migrates to the high temperature area (flame) along the surface of the glass fiber under surface tension and capillary action, forming a path similar to the wax oil being transported along the wick when the candle burns. This phenomenon causes the flame to spread rapidly and the flame retardant effect is greatly reduced. Although glass fiber can significantly improve the mechanical properties of the material, the wick effect it causes makes it difficult for traditional flame retardants to meet the flame retardant requirements of glass fiber reinforced polyester composites. Therefore, the development of an efficient flame retardant that can effectively improve the flame retardant properties of polyester materials and overcome the wick effect of the glass fiber reinforced system is still an important research direction in the current flame retardant field.
[0004] DOPO and its derivatives are a class of commonly used flame retardants. For example, in document 1 (Synthesis of DOPO-based polyester polyols and P / N-containing chain extenders and their applications in polyurethane elastomers [D]. Fujian Normal University, 2020.), DOPO was reacted with maleic anhydride (MA) to prepare a DOPO derivative DOPO-MA, which was then reacted with diethylene glycol, ethylene glycol, and adipic acid to synthesize polyester polyols, and finally reacted with 1,3,5-tris(2-hydroxyethyl)isocyanurate (THEIC) to prepare a macromolecular flame retardant. This flame retardant exhibits good flame retardant effects in polyurethane, but its reaction system is complex, the product molecular structure is difficult to control, and the thermal decomposition temperature is low (5% thermal weight loss temperature is 281°C), which cannot meet the requirements of polyester processing conditions, especially in glass fiber reinforced polyester systems, where it is difficult to overcome the candle wick effect.
[0005] Reference 2 (A new halogen-free flame retardant based on 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide for epoxy resins and their carbon fiber composites for the automotive and aviation industries [J]. Macromolecular Materials and Engineering, 2011, 296 (1): 14-30.) designed and prepared a macromolecule containing DOPO and 1,3,5-tris(2-hydroxyethyl)isocyanurate structure, which was applied to epoxy resin and effectively improved the flame retardant properties of the material. However, the molecular weight of the molecule is low, and it is difficult to form a carbon skeleton network during combustion, and the flame retardant effect in glass fiber reinforced polyester is poor.
[0006] In general, the application of DOPO derivative flame retardants in polyester systems, especially glass fiber reinforced polyester systems, generally has the following problems: (1) The reaction system of DOPO derivative flame retardants is complex and the molecular structure is difficult to control; (2) The molecular weight of DOPO derivative flame retardants is not high, and the carbonization effect during the flame retardant process is limited; (3) The thermal decomposition temperature of DOPO derivative flame retardants is low, which is difficult to meet the processing requirements of polyester; (4) The addition of DOPO derivative flame retardants causes severe thermal degradation of polyester during processing and a significant decrease in mechanical properties; (5) The addition of DOPO derivative flame retardants causes a significant candle wick effect during the combustion of glass fiber reinforced polyester materials, and the flame retardant effect is poor. Therefore, although DOPO-based flame retardants have shown certain flame retardant effects in some fields, their application in polyester materials still needs to be further optimized and improved. Summary of the invention
[0007] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a phosphorus-containing macromolecular carbon-forming agent and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] A phosphorus-containing macromolecular carbon-forming agent, the structural formula is as follows:
[0010] ;
[0011] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0012] The structural formula of the dicarboxyl DOPO derivative is as follows:
[0013] .
[0014] As the preferred technical solution:
[0015] The phosphorus-containing macromolecular carbon-forming agent as described above has a 5% thermal weight loss temperature of ≥300°C, a molecular weight of 8000-20000, a phosphorus content of 5000-10000ppm, a nitrogen content of 3000-5000ppm, and an acid value of 4.1-9.9mg KOH / g.
[0016] The present invention also provides a method for preparing a phosphorus-containing macromolecular carbon-forming agent as described in any one of the above items, the reaction equation is as follows Figure 4 As shown, the following steps are included:
[0017] (a) mixing a dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate uniformly and melting the mixture at 150-220° C.;
[0018] (b) adding the first catalyst to the system of step (a), stirring and reacting for 2-4 hours, during which time vacuum is continuously drawn to remove water produced by the reaction;
[0019] The first catalyst is added after melting in the present invention to prevent the first catalyst from adhering to the inner wall of the reaction container with the reactants during the melting process and being unable to participate in the subsequent reaction, and to prevent the first catalyst from dehydrating the reactants in advance and causing losses.
[0020] (c) After adding sodium bicarbonate to the system of step (b), the reaction is continued with stirring for 0.5-2 hours, and the phosphorus-containing macromolecular carbon-forming agent is obtained through post-treatment (natural cooling, washing, and drying).
[0021] As the preferred technical solution:
[0022] In the above method, in step (a), the reaction equation for preparing the dicarboxyl DOPO derivative is as follows: Figure 1 As shown, the specific preparation steps are as follows:
[0023] (i) dissolving DOPO and glyoxal in a solvent (toluene, anhydrous ethanol, acetonitrile, xylene, anhydrous methanol, acetone, dimethyl sulfoxide or N,N-dimethylformamide), reflux at 90-110° C. for 3 h, filtering, washing and drying to obtain a white product;
[0024] (ii) uniformly mixing the product obtained in step (i) with adipic acid and melting the mixture at 180-220° C.;
[0025] (iii) adding the second catalyst to the system of step (ii), stirring the reaction for 3-5 hours, during which nitrogen is continuously passed to remove water produced by the reaction, and post-treating (washing, drying) to obtain a dicarboxyl DOPO derivative;
[0026] The second catalyst is added after melting to prevent the second catalyst from adhering to the inner wall of the reaction vessel with the reactants during the melting process and being unable to participate in subsequent reactions, and to prevent the second catalyst from dehydrating the reactants in advance and causing losses.
[0027] In the method described above, during the preparation of the dicarboxyl DOPO derivative, the molar ratio of DOPO to glyoxal is 1.5-10:1; the molar ratio of the product obtained in step (i) to adipic acid is 1:1.5-10; the second catalyst is p-toluenesulfonic acid or zinc acetate, and the mass addition amount of the second catalyst is 0.1-1% of the total mass addition amount of DOPO, glyoxal and adipic acid.
[0028] According to the method described above, in the preparation process of the phosphorus-containing macromolecular carbon-forming agent, the molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 1-5:1:1-5; the first catalyst is concentrated sulfuric acid, p-toluenesulfonic acid or phosphoric acid, and the mass addition amount of the first catalyst is 0.1-1% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate; the mass addition amount of sodium bicarbonate is 0.1-5% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate.
[0029] The present invention also provides a flame retardant glass fiber reinforced polyester resin composition using a phosphorus-containing macromolecular carbon-forming agent as described in any of the above items, which is composed of 60-80 parts of polyester resin, 15-30 parts of glass fiber, 2.5-4 parts of aluminum phosphite, and 5-10 parts of phosphorus-containing macromolecular carbon-forming agent in parts by weight, and there is no crystal water in the aluminum phosphite; the aluminum phosphite (produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S) used in the present invention has no crystal water, excellent thermal stability, 1% thermal weight loss decomposition temperature is greater than 420°C (TGA, 10°C / min, N2), and the residual mass at 800°C is greater than 95% (TGA, 10°C / min, N2).
[0030] As the preferred technical solution:
[0031] In the flame-retardant glass fiber reinforced polyester resin composition as described above, the polyester resin is one or more of polyethylene terephthalate and polybutylene terephthalate; the glass fiber is alkali-free glass fiber with a length of 1.5-5.0 mm; wherein the glass fiber is used as a reinforcing material to improve the mechanical properties of the material.
[0032] The present invention also provides a flame retardant polyester composite material, which is prepared by melt blending a flame retardant glass fiber reinforced polyester resin composition as described above, followed by cooling, drying, pelletizing and injection molding, wherein the melt blending temperature is 230-280°C.
[0033] As the preferred technical solution:
[0034] The flame-retardant polyester composite material as described above produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of ≥30.5%, a tensile strength of 100-150 MPa, a flexural strength of 150-180 MPa, and a simply supported beam notched impact strength of 7-9 KJ / m 2 ;
[0035] The tensile strength, flexural strength and simply supported beam notched impact strength of the flame-retardant polyester composite material of the present invention are all reduced by less than 10% compared with the polyester composite material without adding flame-retardant components. This is because the phosphorus-containing macromolecular carbon-forming agent in the flame-retardant polyester composite material has good compatibility with polyester and has little effect on the mechanical properties of the polyester matrix.
[0036] Principle of the invention:
[0037] 1. Targeting the problem (1) The reaction system of DOPO derivative flame retardants is complex and the molecular structure is difficult to control:
[0038] The present invention first uses a DOPO diol derivative (i.e., the white product of step (i)) to esterify with adipic acid to prepare a dicarboxyl DOPO derivative, then performs an esterification reaction with 1,3,5-tris(2-hydroxyethyl)isocyanurate to form a macromolecular structure, and finally performs sodium saltization of the terminal carboxyl group to obtain a phosphorus-containing macromolecular carbon-forming agent. The phosphorus-containing macromolecular carbon-forming agent prepared by the method of two successive esterifications has a controllable molecular structure, few side reactions, and a high product purity.
[0039] 2. Regarding problem (2) that the molecular weight of DOPO derivative flame retardants is not high, and the carbonization effect during the flame retardant process is limited; and problem (3) that the thermal decomposition temperature of DOPO derivative flame retardants is low, which is difficult to meet the requirements of polyester processing:
[0040] The two ends of the dicarboxyl DOPO derivative of the present invention have aliphatic long-chain terminal carboxyl groups with a carbon number of 6, and exhibit extremely high reactivity with 1,3,5-tris(2-hydroxyethyl)isocyanurate. The phosphorus-containing macromolecular carbon-forming agent generated by the reaction has a high molecular weight and forms a three-dimensional network structure. As the esterification reaction proceeds and the molecular weight increases, the steric hindrance effect of the substituent in the molecule is enhanced, and the intermolecular force is also increased, which makes the O=PO bond in the structure of the dicarboxyl DOPO derivative more stable and difficult to break, thereby significantly increasing the thermal decomposition temperature of the phosphorus-containing macromolecular carbon-forming agent.
[0041] 3. Regarding problem (4), adding DOPO derivative flame retardants causes severe thermal degradation of polyester during processing and a significant decrease in mechanical properties:
[0042] The use of conventional DOPO derivatives as flame retardants will lead to aggravated thermal degradation of polyester during processing, thereby significantly reducing its mechanical properties. The present invention finds that the main reason is that conventional DOPO derivatives have a low molecular weight and contain a large number of terminal hydroxyl groups or terminal carboxyl groups, and such groups will promote the hydrolysis reaction of ester bonds in polyester during polyester thermal processing, thereby causing severe thermal degradation. The present invention adds sodium bicarbonate to the system for preparing a phosphorus-containing macromolecular carbonizing agent, replaces the terminal carboxyl group with a sodium salt, and prepares a phosphorus-containing macromolecular carbonizing agent, which effectively reduces the promotion effect of the terminal carboxyl group on thermal degradation during polyester processing.
[0043] IV: Regarding issue (5), adding DOPO derivative flame retardants will cause a significant candle wick effect during the combustion of glass fiber reinforced polyester materials, resulting in poor flame retardant effect:
[0044] Usually, aluminum phosphite is prepared by the reaction of phosphorous acid and aluminum hydroxide, with the chemical formula of Al2(HPO3)3·3H2O, and the theoretical content of crystal water is 15.5%. It cannot be used directly as a flame retardant, and its crystal water is difficult to completely remove through conventional processes. Even if it is dried at 240℃ for 8 hours under vacuum conditions, the crystal water content remains at around 2-3%, resulting in its 1% thermal decomposition temperature (TGA, 10℃ / min, N2) being difficult to exceed 250℃, so it can only be used as a flame retardant synergist. When conventional aluminum phosphite is added to polyester materials, its crystal water will generate a large amount of water vapor during the combustion process, destroying the density of the carbon layer, causing the combustion elements (oxygen, combustibles, heat) inside and outside the combustion environment to continue to exchange, thus failing to achieve the purpose of flame retardancy.
[0045] Conventional phosphorus-containing flame retardants have low molecular weight and contain a large number of terminal hydroxyl or terminal carboxyl groups, which will cause the ester bonds in the polyester to undergo hydrolysis during the thermal processing of polyester, and fail to achieve the purpose of promoting droplets and effective carbonization. In addition, the carbon formed by conventional phosphorus-containing flame retardants cannot effectively cover the surface of the glass fiber, resulting in a significant candle wick effect, making it difficult to achieve a good flame retardant effect.
[0046] The aluminum phosphite used in the present invention has no crystal water, and the phosphorus-containing macromolecular carbon-forming agent and the aluminum phosphite play a synergistic role in the combustion process, promote the formation of a carbon layer in the combustion process, and greatly improve the density of the carbon layer, thereby achieving the effect of flameless molten droplets. Specifically: the phosphorus-containing macromolecular carbon-forming agent is a three-dimensional network structure, and has a high molecular weight, and contains a large number of ester bonds and aromatic ring structures in the molecule, which can be dehydrated and catalyzed into carbon by the phosphoric acid generated in the combustion process, forming a network carbon skeleton wrapped on the glass fiber, destroying the glass fiber candle wick effect, and then the aluminum phosphite with high thermal stability migrates and fills in the carbon skeleton to form a dense phosphorus-containing carbon layer. At the same time, because the end group of the phosphorus-containing macromolecular carbon-forming agent is treated with sodium salt, the sodium salt structure can promote the breakage of the molecular chain of polyester during the combustion process, accelerate the generation of fine molten droplets during the combustion process, and thus play the role of promoting molten droplets. The dense phosphorus-containing carbon layer covers the surface of the tiny molten droplets and fills the inside thereof, so that the flame is quickly extinguished during the dripping process of the molten droplets, forming flameless molten droplets, thereby achieving the flame retardant effect of UL94-V0 (molten drop type V0, not completely non-dripping V0), and effectively overcoming the wick effect caused by glass fiber, achieving the purpose of high flame retardant properties of glass fiber reinforced polyester resin composition at low addition amount.
[0047] The flame retardant polyester composite material is prepared by melt-blending polyester resin, glass fiber, aluminum phosphite and phosphorus-containing macromolecular carbon-forming agent in a certain proportion. During the combustion of polyester, the flame retardant aluminum phosphite can promote the dehydration of polyester into carbon, and the phosphorus-containing macromolecular carbon-forming agent provides a carbon source, which can effectively improve the density of the carbon layer. At the same time, the introduced sodium salt structure mainly plays a role in promoting melting droplets during the combustion of polyester. The above components play a synergistic role during the combustion of polyester, thereby effectively improving the flame retardant performance of the polyester material.
[0048] Beneficial effects:
[0049] The invention adopts a double esterification method to prepare a phosphorus-containing macromolecular carbon-forming agent, which has the characteristics of controllable reaction, controllable molecular structure, few side reactions and high product purity. The prepared phosphorus-containing macromolecular carbon-forming agent has a high molecular weight and its 5% thermal weight loss temperature can reach above 300°C.
[0050] The flame-retardant polyester composite material of the present invention significantly improves the flame retardant properties of the polyester material through the synergistic effect of the phosphorus-containing macromolecular carbon-forming agent and aluminum phosphite. The material produces flameless droplets when burning, does not ignite absorbent cotton, can meet the UL-94 V-0 test standard at a relatively small addition amount, and effectively overcomes the candle wick effect of glass fiber reinforced polyester material. In addition, the composite material not only has excellent flame retardant effect, but also has less loss of mechanical properties and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The reaction equation for preparing the dicarboxyl DOPO derivative of the present invention;
[0052] Figure 2 This is the infrared spectrum of the dicarboxyl DOPO derivative prepared in Example 1 of the present invention;
[0053] Figure 3 This is the H-NMR spectrum of the dicarboxyl DOPO derivative prepared in Example 1 of the present invention;
[0054] Figure 4 The reaction equation for preparing the phosphorus-containing macromolecular carbon-forming agent of the present invention;
[0055] Figure 5 Infrared spectrum of the phosphorus-containing macromolecular carbon-forming agent prepared in Example 1 of the present invention;
[0056] Figure 6 This is the hydrogen NMR spectrum of the phosphorus-containing macromolecular carbon-forming agent prepared in Example 1 of the present invention, wherein 7-8.5ppm is the chemical shift of hydrogen on the DOPO aromatic ring structure, 4-5ppm is the chemical shift of hydrogen on C in the methylene and CP bonds in 1,3,5-tris(2-hydroxyethyl)isocyanurate, and 1-3ppm is the chemical shift of hydrogen on the methylene in adipic acid and succinic acid. DETAILED DESCRIPTION
[0057] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0058] The following are the methods for testing the relevant performance indicators in the embodiments and comparative examples:
[0059] 5% thermal weight loss temperature of phosphorus-containing macromolecular carbonizing agent: Tested in accordance with GB / T 33047.1-2016 "Thermogravimetry (TG) of Plastic Polymers Part 1: General Rules";
[0060] Molecular weight of phosphorus-containing macromolecular carbon-forming agent: Tested in accordance with GB / T 36214.1-2018 "Determination of average molecular weight and molecular weight distribution of polymers by size exclusion chromatography of plastics Part 1: General rules";
[0061] Phosphorus content of phosphorus-containing macromolecular carbonizing agents: Tested in accordance with JY / T 015-1996 "General Rules for Inductively Coupled Plasma Atomic Emission Spectrometry";
[0062] Nitrogen content of phosphorus-containing macromolecular carbon-forming agents: Tested in accordance with ASTM D5291-21 "Standard Test Method for Carbon, Hydrogen, and Nitrogen Content in Petroleum Products and Lubricants (Elemental Analyzer Method)";
[0063] Acid value of phosphorus-containing macromolecular carbonizing agent: Tested in accordance with GB / T 2895-2008 "Determination of partial acid value and total acid value of plastic polyester resin";
[0064] Limiting oxygen index of flame retardant polyester composite materials: Tested in accordance with GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test";
[0065] Tensile strength of flame-retardant polyester composites: tested in accordance with GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles";
[0066] Flexural strength of flame-retardant polyester composite materials: tested in accordance with GB / T 9341-2008 "Determination of flexural properties of plastics";
[0067] The notched impact strength of flame-retardant polyester composite materials is tested with reference to GB / T 1043.1-2008 “Determination of impact properties of plastics - Part 1: Non-instrumented impact test”.
[0068] Example 1
[0069] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0070] (1) Raw material preparation:
[0071] DOPO;
[0072] Glyoxal;
[0073] Adipic acid;
[0074] Succinic acid;
[0075] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0076] Sodium bicarbonate;
[0077] First catalyst: concentrated sulfuric acid (mass fraction 98%);
[0078] Second catalyst: p-toluenesulfonic acid;
[0079] Solvent: toluene;
[0080] (2) Preparation of dicarboxyl DOPO derivatives:
[0081] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 100 °C for 3 h, filtered, washed and dried to obtain a white product;
[0082] Among them, the molar ratio of DOPO to glyoxal is 2:1;
[0083] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 180° C.;
[0084] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:1.5;
[0085] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 1% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 3 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, a dicarboxyl DOPO derivative is obtained;
[0086] The obtained dicarboxyl DOPO derivative has the structural formula:
[0087] ;
[0088] The infrared spectrum and H-NMR spectrum of the dicarboxyl DOPO derivative are shown in Figure 2 , Figure 3 As shown;
[0089] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0090] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 190°C;
[0091] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 2:1:1;
[0092] (3.2) After adding the first catalyst to the system of step (3.1), stirring and reacting for 4 hours, during which time vacuum is continuously applied to remove the water produced by the reaction;
[0093] The mass addition amount of the first catalyst is 0.8% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0094] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 3% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is continued with stirring for 1.5 hours. After natural cooling, washing and drying, the phosphorus-containing macromolecular carbonizing agent is obtained.
[0095] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0096] ;
[0097] In the formula, -C=O- and -COO- The invention is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid; its infrared spectrum and nuclear magnetic hydrogen spectrum are as follows: Figure 5 , Figure 6 As shown;
[0098] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is 325°C, the molecular weight is 10470, the phosphorus content is 8320ppm, the nitrogen content is 4180ppm, and the acid value is 7.7mg KOH / g.
[0099] Example 2
[0100] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0101] (1) Raw material preparation:
[0102] DOPO;
[0103] Glyoxal;
[0104] Adipic acid;
[0105] Succinic acid;
[0106] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0107] Sodium bicarbonate;
[0108] First catalyst: p-toluenesulfonic acid;
[0109] Second catalyst: zinc acetate;
[0110] Solvent: anhydrous ethanol;
[0111] (2) Preparation of dicarboxyl DOPO derivatives:
[0112] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 90 °C for 3 h, filtered, washed and dried to obtain a white product;
[0113] Among them, the molar ratio of DOPO to glyoxal is 3:1;
[0114] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 190° C.;
[0115] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:10;
[0116] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 0.1% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 3.5 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, the dicarboxyl DOPO derivative is obtained;
[0117] The obtained dicarboxyl DOPO derivative has the structural formula:
[0118] ;
[0119] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0120] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 160°C;
[0121] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 1:1:1;
[0122] (3.2) After adding the first catalyst to the system of step (3.1), the reaction was stirred for 2.5 hours, during which vacuum was continuously drawn to remove the water produced by the reaction;
[0123] The mass addition amount of the first catalyst is 0.5% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0124] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 2% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is continued with stirring for 1 hour. After natural cooling, washing and drying, the phosphorus-containing macromolecular carbon-forming agent is obtained.
[0125] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0126] ;
[0127] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0128] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is 330°C, the molecular weight is 12770, the phosphorus content is 6510ppm, the nitrogen content is 3960ppm, and the acid value is 6.1mg KOH / g.
[0129] Example 3
[0130] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0131] (1) Raw material preparation:
[0132] DOPO;
[0133] Glyoxal;
[0134] Adipic acid;
[0135] Succinic acid;
[0136] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0137] Sodium bicarbonate;
[0138] First catalyst: phosphoric acid (mass fraction 85%);
[0139] Second catalyst: p-toluenesulfonic acid;
[0140] Solvent: acetonitrile;
[0141] (2) Preparation of dicarboxyl DOPO derivatives:
[0142] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 90 °C for 3 h, filtered, washed and dried to obtain a white product;
[0143] Wherein, the molar ratio of DOPO to glyoxal is 1.5:1;
[0144] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 200° C.;
[0145] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:2;
[0146] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 0.5% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 4.5 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, the dicarboxyl DOPO derivative is obtained;
[0147] The obtained dicarboxyl DOPO derivative has the structural formula:
[0148] ;
[0149] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0150] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 200°C;
[0151] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 5:1:2;
[0152] (3.2) After adding the first catalyst to the system of step (3.1), stirring and reacting for 4 hours, during which time vacuum is continuously applied to remove the water produced by the reaction;
[0153] The mass addition amount of the first catalyst is 1% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0154] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 5% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is stirred for 2 hours. After natural cooling, washing and drying, the phosphorus-containing macromolecular carbonizing agent is obtained.
[0155] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0156] ;
[0157] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0158] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbon-forming agent is 310°C, the molecular weight is 8000, the phosphorus content is 9970ppm, the nitrogen content is 3020ppm, and the acid value is 9.9mg KOH / g.
[0159] Example 4
[0160] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0161] (1) Raw material preparation:
[0162] DOPO;
[0163] Glyoxal;
[0164] Adipic acid;
[0165] Succinic acid;
[0166] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0167] Sodium bicarbonate;
[0168] First catalyst: p-toluenesulfonic acid;
[0169] Second catalyst: p-toluenesulfonic acid;
[0170] Solvent: acetone;
[0171] (2) Preparation of dicarboxyl DOPO derivatives:
[0172] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 90 °C for 3 h, filtered, washed and dried to obtain a white product;
[0173] The molar ratio of DOPO to glyoxal is 10:1;
[0174] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 210° C.;
[0175] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:5;
[0176] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 0.1% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 5 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, the dicarboxyl DOPO derivative is obtained;
[0177] The obtained dicarboxyl DOPO derivative has the structural formula:
[0178] ;
[0179] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0180] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 170°C;
[0181] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 5:1:5;
[0182] (3.2) After adding the first catalyst to the system of step (3.1), stirring and reacting for 2 hours, during which time vacuum is continuously applied to remove the water produced by the reaction;
[0183] The mass addition amount of the first catalyst is 0.1% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0184] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 1% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is stirred for 0.5 h, and after natural cooling, washing and drying, the phosphorus-containing macromolecular carbonizing agent is obtained.
[0185] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0186] ;
[0187] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0188] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is 332°C, the molecular weight is 15320, the phosphorus content is 7790ppm, the nitrogen content is 4300ppm, and the acid value is 5.4mg KOH / g.
[0189] Example 5
[0190] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0191] (1) Raw material preparation:
[0192] DOPO;
[0193] Glyoxal;
[0194] Adipic acid;
[0195] Succinic acid;
[0196] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0197] Sodium bicarbonate;
[0198] First catalyst: p-toluenesulfonic acid;
[0199] Second catalyst: zinc acetate;
[0200] Solvent: dimethyl sulfoxide;
[0201] (2) Preparation of dicarboxyl DOPO derivatives:
[0202] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 110 °C for 3 h, filtered, washed and dried to obtain a white product;
[0203] Wherein, the molar ratio of DOPO to glyoxal is 1.5:1;
[0204] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 220° C.;
[0205] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:6;
[0206] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 0.3% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 3.2 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, the dicarboxyl DOPO derivative is obtained;
[0207] The obtained dicarboxyl DOPO derivative has the structural formula:
[0208] ;
[0209] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0210] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 190°C;
[0211] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 3:1:4;
[0212] (3.2) After adding the first catalyst to the system of step (3.1), stirring and reacting for 2 hours, during which time vacuum is continuously applied to remove the water produced by the reaction;
[0213] The mass addition amount of the first catalyst is 0.2% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0214] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 0.1% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is continued with stirring for 0.5 h. After natural cooling, washing and drying, the phosphorus-containing macromolecular carbonizing agent is obtained.
[0215] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0216] ;
[0217] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0218] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is 350°C, the molecular weight is 19860, the phosphorus content is 5630ppm, the nitrogen content is 4980ppm, and the acid value is 4.1mg KOH / g.
[0219] Example 6
[0220] A method for preparing a phosphorus-containing macromolecular carbon-forming agent, the specific steps are:
[0221] (1) Raw material preparation:
[0222] DOPO;
[0223] Glyoxal;
[0224] Adipic acid;
[0225] Succinic acid;
[0226] 1,3,5-Tris(2-hydroxyethyl)isocyanurate;
[0227] Sodium bicarbonate;
[0228] First catalyst: phosphoric acid (mass fraction 85%);
[0229] Second catalyst: p-toluenesulfonic acid;
[0230] Solvent: N,N-dimethylformamide;
[0231] (2) Preparation of dicarboxyl DOPO derivatives:
[0232] (2.1) DOPO and glyoxal were dissolved in a solvent, refluxed at 110 °C for 3 h, filtered, washed and dried to obtain a white product;
[0233] Among them, the molar ratio of DOPO to glyoxal is 4:1;
[0234] (2.2) uniformly mixing the product obtained in step (2.1) with adipic acid and melting the mixture at 190° C.;
[0235] Wherein, the molar ratio of the product obtained in step (2.1) to adipic acid is 1:3;
[0236] (2.3) After adding the second catalyst to the system of step (2.2) (the mass amount of the second catalyst added is 0.2% of the total mass amount of DOPO, glyoxal and adipic acid added), stirring the reaction for 4 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and after washing and drying, the dicarboxyl DOPO derivative is obtained;
[0237] The obtained dicarboxyl DOPO derivative has the structural formula:
[0238] ;
[0239] (3) Preparation of phosphorus-containing macromolecular carbon-forming agent:
[0240] (3.1) Mix the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate and melt them at 180°C;
[0241] The molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 2:1:3;
[0242] (3.2) After adding the first catalyst to the system of step (3.1), the reaction was stirred for 2.2 hours, during which vacuum was continuously drawn to remove the water produced by the reaction;
[0243] The mass addition amount of the first catalyst is 0.3% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate;
[0244] (3.3) After adding sodium bicarbonate to the system of step (3.2) (the mass amount of sodium bicarbonate added is 0.4% of the total mass amount of the dicarboxy DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate added), the reaction is stirred for 1 hour, and after natural cooling, washing and drying, the phosphorus-containing macromolecular carbonizing agent is obtained.
[0245] The final prepared phosphorus-containing macromolecular carbonizing agent has the following structural formula:
[0246] ;
[0247] In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid;
[0248] The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is 348°C, the molecular weight is 19570, the phosphorus content is 5250ppm, the nitrogen content is 4870ppm, and the acid value is 4.2mg KOH / g.
[0249] Example 7
[0250] A flame retardant polyester composite material, comprising the following specific steps:
[0251] (1) Raw material preparation:
[0252] Polyester resin: polyethylene terephthalate;
[0253] Glass fiber: Alkali-free glass fiber, average length is 2.3mm;
[0254] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0255] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 1;
[0256] (2) Preparation of flame-retardant glass fiber reinforced polyester resin composition:
[0257] By weight, weigh 77.5 parts of polyester resin, 15 parts of glass fiber, 2.5 parts of aluminum phosphite, and 5 parts of phosphorus-containing macromolecular carbon-forming agent;
[0258] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0259] (3) Preparation of flame-retardant polyester composite materials:
[0260] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 280° C. and then cooled, dried, pelletized and injection-molded in sequence.
[0261] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 30.5%, a tensile strength of 110MPa, a flexural strength of 162MPa, and a simply supported beam notched impact strength of 7.5KJ / m 2 .
[0262] Example 8
[0263] A flame retardant polyester composite material, comprising the following specific steps:
[0264] (1) Raw material preparation:
[0265] Polyester resin: polybutylene terephthalate;
[0266] Glass fiber: Alkali-free glass fiber, average length is 3.8mm;
[0267] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0268] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 2;
[0269] (2) Preparation of flame retardant glass fiber reinforced polyester resin composition:
[0270] According to weight, weigh 70 parts of polyester resin, 16 parts of glass fiber, 4 parts of aluminum phosphite, and 10 parts of phosphorus-containing macromolecular carbon-forming agent;
[0271] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0272] (3) Preparation of flame-retardant polyester composite materials:
[0273] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 230° C. and then cooled, dried, pelletized and injection-molded in sequence.
[0274] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 35.5%, a tensile strength of 100MPa, a flexural strength of 150MPa, and a simply supported beam notched impact strength of 7KJ / m 2 .
[0275] Example 9
[0276] A flame retardant polyester composite material, comprising the following specific steps:
[0277] (1) Raw material preparation:
[0278] Polyester resin: a mixture of polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 1:1;
[0279] Glass fiber: Alkali-free glass fiber, average length is 1.7mm;
[0280] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0281] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 3;
[0282] (2) Preparation of flame retardant glass fiber reinforced polyester resin composition:
[0283] By weight, weigh 61 parts of polyester resin, 30 parts of glass fiber, 3 parts of aluminum phosphite, and 6 parts of phosphorus-containing macromolecular carbon-forming agent;
[0284] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0285] (3) Preparation of flame-retardant polyester composite materials:
[0286] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 260° C. and then cooled, dried, pelletized and injection-molded in sequence.
[0287] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 33.5%, a tensile strength of 150 MPa, a flexural strength of 180 MPa, and a simply supported beam notched impact strength of 9 KJ / m 2 .
[0288] Example 10
[0289] A flame retardant polyester composite material, comprising the following specific steps:
[0290] (1) Raw material preparation:
[0291] Polyester resin: a mixture of polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 4:1;
[0292] Glass fiber: Alkali-free glass fiber, average length is 1.5mm;
[0293] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0294] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 4;
[0295] (2) Preparation of flame retardant glass fiber reinforced polyester resin composition:
[0296] According to weight, weigh 70 parts of polyester resin, 21.5 parts of glass fiber, 3.5 parts of aluminum phosphite, and 5 parts of phosphorus-containing macromolecular carbon-forming agent;
[0297] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0298] (3) Preparation of flame-retardant polyester composite materials:
[0299] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 270° C. and then cooled, dried, pelletized and injection-molded in sequence to obtain the flame retardant glass fiber reinforced polyester resin composition.
[0300] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 32%, a tensile strength of 129 MPa, a flexural strength of 168 MPa, and a simply supported beam notched impact strength of 7.8 KJ / m 2 .
[0301] Embodiment 11
[0302] A flame retardant polyester composite material, comprising the following specific steps:
[0303] (1) Raw material preparation:
[0304] Polyester resin: a mixture of polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 1:1.5;
[0305] Glass fiber: Alkali-free glass fiber, average length is 5mm;
[0306] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0307] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 5;
[0308] (2) Preparation of flame retardant glass fiber reinforced polyester resin composition:
[0309] According to weight, weigh 75 parts of polyester resin, 15.5 parts of glass fiber, 2.5 parts of aluminum phosphite, and 7 parts of phosphorus-containing macromolecular carbon-forming agent;
[0310] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0311] (3) Preparation of flame-retardant polyester composite materials:
[0312] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 260° C. and then cooled, dried, pelletized and injection-molded in sequence.
[0313] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 34.5%, a tensile strength of 108MPa, a flexural strength of 159MPa, and a simply supported beam notched impact strength of 7.4KJ / m 2 .
[0314] Comparative Example 1
[0315] A polyester composite material is basically the same as Example 11, except that: in this comparative example, a carbon-forming agent TMA (from the literature: A novel phosphorus / nitrogen-containing polycarboxylic acid endowing epoxy resin withexcellent flame retardance and mechanical properties[J].Chemical EngineeringJournal, 2019, 375: 121916.) prepared by reacting DOPO, maleic anhydride (MA) and 1,3,5-tris(2-hydroxyethyl)isocyanurate is used to replace the phosphorus-containing macromolecular carbon-forming agent in Example 11.
[0316] The resulting polyester composite material produced flaming droplets during combustion, igniting the absorbent cotton, and did not meet the UL-94V-0 test standard. The limiting oxygen index was 30%, the tensile strength was 81MPa, the flexural strength was 127MPa, and the simply supported beam notched impact strength was 6.5KJ / m 2 .
[0317] Comparative Example 2
[0318] A polyester composite material is basically the same as Example 11, except that: this comparative example uses a carbon-forming agent IPDI-DOPO-HQ-THEIC (from the literature: Research on the preparation of phosphorus-containing flame-retardant epoxy resin [D]. Shanghai University of Technology, 2020.) prepared by reacting DOPO-DQ, isophorone diisocyanate (IPDI), and 1,3,5-tris(2-hydroxyethyl)isocyanurate to replace the phosphorus-containing macromolecular carbon-forming agent in Example 11.
[0319] The resulting polyester composite material produced flaming droplets during combustion, igniting the absorbent cotton, and did not meet the UL-94V-0 test standard. The limiting oxygen index was 28.5%, the tensile strength was 93MPa, the flexural strength was 131MPa, and the simply supported beam notched impact strength was 7.3KJ / m 2 .
[0320] It can be seen from the results of Example 11, Comparative Example 1 and Comparative Example 2 that, compared with Example 11, the flame retardant properties and mechanical properties of the polyester composite materials obtained in Comparative Example 1 and Comparative Example 2 are worse. The reasons are as follows: the carbon-forming agent obtained in the comparative example has a low molecular weight and contains a large number of terminal carboxyl structures, which easily promote the thermal degradation of polyester during processing, thereby reducing its mechanical strength; at the same time, the carbon-forming agent in the comparative example does not introduce a sodium salt structure, while the sodium salt can promote the formation of fine molten droplets when the polyester resin burns; due to the lack of this structure, the droplet-promoting performance of the carbon-forming agent in the comparative example is limited; in addition, the low molecular weight also makes it difficult for the carbon-forming agent to form a dense carbon layer attached to the surface of the glass fiber, and cannot effectively overcome the wick effect of the glass fiber, which leads to a decrease in flame retardant properties.
[0321] Comparative Example 3
[0322] A polyester composite material, which is substantially the same as Example 11, except that: this comparative example uses a sodium-free phosphorus-containing macromolecular carbon-forming agent to replace the phosphorus-containing macromolecular carbon-forming agent in Example 11;
[0323] The preparation process of the sodium-free phosphorus-containing macromolecular carbon-forming agent is basically the same as that of Example 5, except that step (3.3) is omitted.
[0324] The resulting polyester composite material produced flaming droplets during combustion, igniting the absorbent cotton, and did not meet the UL-94V-0 test standard. The limiting oxygen index was 31%, the tensile strength was 98MPa, the flexural strength was 132MPa, and the simply supported beam notched impact strength was 7.2KJ / m 2 .
[0325] Compared with Example 11, the flame retardant and mechanical properties of the polyester composite material prepared in Comparative Example 3 are worse. The reason is that the charring agent in the comparative example does not introduce the sodium salt structure, while the sodium salt can promote the formation of fine molten droplets of the polyester resin during combustion; due to the lack of this structure, the droplet-promoting performance of the charring agent in the comparative example is limited.
[0326] Example 12
[0327] A flame retardant polyester composite material, comprising the following specific steps:
[0328] (1) Raw material preparation:
[0329] Polyester resin: a mixture of polyethylene terephthalate and polybutylene terephthalate in a mass ratio of 1:7;
[0330] Glass fiber: Alkali-free glass fiber, average length is 4.3mm;
[0331] Aluminum phosphite: produced by Hunan Meilaipo Technology Development Co., Ltd. / Shanghai Lidao New Materials Technology Co., Ltd., brand M119-S, no crystal water;
[0332] Phosphorus-containing macromolecular carbon-forming agent: prepared in Example 6;
[0333] (2) Preparation of flame retardant glass fiber reinforced polyester resin composition:
[0334] By weight, weigh 65 parts of polyester resin, 22.5 parts of glass fiber, 3.5 parts of aluminum phosphite, and 9 parts of phosphorus-containing macromolecular carbon-forming agent;
[0335] The flame retardant glass fiber reinforced polyester resin composition is obtained by uniformly mixing;
[0336] (3) Preparation of flame-retardant polyester composite materials:
[0337] The flame retardant glass fiber reinforced polyester resin composition is melt-blended at 240° C. and then cooled, dried, pelletized and injection-molded in sequence.
[0338] The flame-retardant polyester composite material finally produced produces flameless droplets during combustion, does not ignite absorbent cotton, meets the UL-94 V-0 test standard, has a limiting oxygen index of 35%, a tensile strength of 138MPa, a flexural strength of 172MPa, and a simply supported beam notched impact strength of 8.2KJ / m 2.
[0339] Comparative Example 4
[0340] A polyester composite material is basically the same as Example 12, except that: this comparative example uses polyaluminum phosphite (containing crystal water) produced by Shenzhen Ruishixing Technology Co., Ltd. to replace the aluminum phosphite in Example 12.
[0341] The polyester composite material finally obtained produced flaming droplets during the combustion process, which ignited the absorbent cotton and did not meet the UL-94V-0 test standard, with a limiting oxygen index of 30%.
[0342] Compared with Example 12, the flame retardant properties of the polyester composite material prepared in Comparative Example 4 deteriorate. The reason is that the aluminum phosphite contains 2% of crystal water. During the combustion process, the crystal water will generate a large amount of water vapor, which will destroy the density of the carbon layer and enable the combustion elements (oxygen, combustibles, heat) inside and outside the combustion environment to be continuously exchanged, thereby resulting in a decrease in flame retardant properties.
Claims
1. A phosphorus-containing macromolecular carbon-forming agent, characterized in that: The structural formula is as follows: ; In the formula, -C=O- and -COO- It is composed of 2 to 7 segments, each of which is independently selected from one of the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and a dicarboxyl DOPO derivative and the segments of the esterification product of 1,3,5-tris(2-hydroxyethyl)isocyanurate and succinic acid; The structural formula of the dicarboxyl DOPO derivative is as follows: 。 2. A phosphorus-containing macromolecular carbon-forming agent according to claim 1, characterized in that: The 5% thermal weight loss temperature of the phosphorus-containing macromolecular carbonizing agent is ≥300°C, the molecular weight is 8000-20000, the phosphorus content is 5000-10000ppm, the nitrogen content is 3000-5000ppm, and the acid value is 4.1-9.9mg KOH / g.
3. A method for preparing a phosphorus-containing macromolecular carbon-forming agent as claimed in claim 1 or 2, characterized in that: The following steps are involved: (a) mixing a dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate uniformly and melting the mixture at 150-220° C.; (b) adding the first catalyst to the system of step (a), stirring and reacting for 2-4 hours, during which time vacuum is continuously drawn to remove water produced by the reaction; (c) After adding sodium bicarbonate to the system of step (b), the reaction is continued with stirring for 0.5-2 hours, and the phosphorus-containing macromolecular carbon-forming agent is obtained through post-treatment.
4. The method according to claim 3, characterized in that In step (a), the preparation steps of the dicarboxyl DOPO derivative are as follows: (i) dissolving DOPO and glyoxal in a solvent, reflux at 90-110° C. for 3 h, filtering, washing and drying to obtain a product; (ii) uniformly mixing the product obtained in step (i) with adipic acid and melting the mixture at 180-220° C.; (iii) After adding the second catalyst to the system of step (ii), stirring the reaction for 3-5 hours, during which nitrogen is continuously passed to remove the water produced by the reaction, and the dicarboxyl DOPO derivative is obtained after post-treatment.
5. The method according to claim 4, characterized in that In the preparation process of the dicarboxyl DOPO derivative, the molar ratio of DOPO to glyoxal is 1.5-10:1; the molar ratio of the product obtained in step (i) to adipic acid is 1:1.5-10; the second catalyst is p-toluenesulfonic acid or zinc acetate, and the mass addition amount of the second catalyst is 0.1-1% of the total mass addition amount of DOPO, glyoxal and adipic acid.
6. The method according to claim 3, characterized in that: In the preparation process of the phosphorus-containing macromolecular carbon-forming agent, the molar ratio of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate is 1-5:1:1-5; the first catalyst is concentrated sulfuric acid, p-toluenesulfonic acid or phosphoric acid, and the mass addition amount of the first catalyst is 0.1-1% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid and 1,3,5-tris(2-hydroxyethyl)isocyanurate; the mass addition amount of sodium bicarbonate is 0.1-5% of the total mass addition amount of the dicarboxyl DOPO derivative, succinic acid, 1,3,5-tris(2-hydroxyethyl)isocyanurate and sodium bicarbonate.
7. A flame retardant glass fiber reinforced polyester resin composition using a phosphorus-containing macromolecular carbon-forming agent as claimed in claim 1 or 2, characterized in that: The invention is composed of 60-80 parts of polyester resin, 15-30 parts of glass fiber, 2.5-4 parts of aluminum phosphite and 5-10 parts of phosphorus-containing macromolecular carbon-forming agent by weight, and the aluminum phosphite contains no crystal water.
8. The flame retardant glass fiber reinforced polyester resin composition according to claim 7, characterized in that: The polyester resin is one or more of polyethylene terephthalate and polybutylene terephthalate; the glass fiber is alkali-free glass fiber with a length of 1.5-5.0 mm.
9. A flame retardant polyester composite material, characterized in that: The flame retardant glass fiber reinforced polyester resin composition according to claim 7 or 8 is prepared by melt blending and then cooling, drying, pelletizing and injection molding in sequence, wherein the melt blending temperature is 230-280°C.
10. The flame retardant polyester composite material according to claim 9, characterized in that: Flame-retardant polyester composite materials produce flameless droplets during combustion, do not ignite absorbent cotton, meet UL-94 V-0 test standards, limit oxygen index ≥ 30.5%, tensile strength of 100-150MPa, flexural strength of 150-180MPa, simple beam notched impact strength of 7-9KJ / m 2 .
Citation Information
Patent Citations
Modified benzoxazine resin and composition application thereof
CN106188538A
Maleimide resin, curable resin composition, and cured object obtained therefrom
WO2020213639A1
Aromatic-amine resin, maleimide resin, curable resin composition, and cured object obtained therefrom
WO2020213640A1